The Ukrainian Association of Psychosomatic Medicine: from the history of creation to the present through the pandemic and war - Leshchuk, Ірина; Chaban, Олег; Khaustova, Олена; Frankova, Ірина (Psychosomatic Medicine and General Practice, 2024)
The Ukrainian Association of Psychosomatic Medicine (UPMA) is a professional scientific organization in the field of health care that unites specialists with different profiles who work in the field of psychosomatic medicine throughout Ukraine. UPMA was created in 2016 and currently has more than 120 members. The goal of VAPSM is to implement a multidisciplinary approach in medicine, to carry out educational work for the population and educational work for medical professionals. This article provides information on the activities of UPMA from the moment of its creation to the present, as well as the impact of the pandemic and the war in Ukraine on the activity and mission of the association.